Implementasi Perda No. 3 Tahun 2005 tentang Zakat dalam Perkembangan Usaha Mikro di Kabupaten Bantaeng - Mahendra, Yusril Ihza; Mustafa, Zulhasari (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This study aims to find out how the management of zakat in Bantaeng Regency is implemented by the local government, as well as how the zakat funds can be used productively in supporting the development of micro businesses for mustahik. Optimal zakat management is not only consumptive, but must also be directed at the aspect of economic empowerment so that mustahik can transform into muzakki in the future. This research uses a qualitative method with a descriptive research type. Data was obtained through field observation techniques, in-depth interviews with related parties, and documentation of the implementation of zakat policies in the region. The results of the study show that the implementation of Bantaeng Regency Regional Regulation Number 3 of 2005 concerning Zakat Management has gone through several main stages, namely: zakat collection, distribution, utilization, reporting, and accountability. The local government through the amil zakat institution has made various efforts to improve the effectiveness of management, including building synergy between Baznas, village governments, and community leaders. One of the prominent forms of zakat utilization is the provision of business capital assistance to mustahik engaged in the micro business sector, such as mobile traders or cart owners around mosques, with a sustainable and community-based approach. The novelty of this research lies in its approach which highlights the function of zakat as an instrument of local economic empowerment based on regional regulations. This shows how zakat is not only a means of charity, but also a strategic tool in alleviating poverty and strengthening the economy of the people at the regional level. These findings make an important contribution to the development of empowerment-based zakat management models in other regions with similar characteristics.